Urban Governance and Sanitation in the Peri-Urban Commune of Agoè-Nyvé 6 in Togo: Diagnosis of the Sanitation System in Adétikopé - (:unkn) unknown (My University, 2023)
Abstract: In African cities, the ever-increasing production of wastewater and excreta poses a major management problem. The aim of this study was to take stock of wastewater and excreta management in Adétikopé in the commune of Agoè-Nyivé 6. This was a cross-sectional, descriptive study of the knowledge, attitudes and practices of the population of the locality of Adétikopé in terms of wastewater and excreta management, which took place from August 2022 to July 2023. It involved 5256 households in 12 villages in the locality of Adétikopé and was carried out via a field survey, interviews, observations and documentary research. The results showed that 72.60% of respondents were women. The majority of households (85.62%) had latrines, 66.40% of which had never been emptied. The remainder used a mechanical emptying truck (5.48%). Households without latrines (14.38%) defecate with neighbors (14.28%) in the open (66.67%) and in public latrines (19.05%). The same applies to wastewater from cooking, washing and dishwashing, which is most often dumped on the public highway (78.77%). Wastewater is a breeding ground for mosquitoes that cause malaria, which is the most common disease in the area. The results of this study show that wastewater and excreta are managed by most concessions in an unhealthy way and discharged into the environment. It is important to step up public awareness campaigns on the harmful consequences of poor wastewater and excreta disposal.
Keywords: African Research